ALGORITMA C4.5 UNTUK PREDIKSI HASIL PEMILIHAN LEGISLATIF DPRD DKI JAKARTA - Evicienna Evicienna; Hilda Amalia (Jurnal Techno Nusa Mandiri, 2013)
Elections are a means of implementation of the sovereignty of the people in the Unitary State of Indonesia based on Pancasila and 1945 Constitution. Elections held in Indonesia is to choose the leadership of both the president and vice president, member of parliament, parliament, and the DPD. The election results should be predicted accurately because of an impact on various aspects of social, economic, security, and others. Based on these problems we need a model that can accurately predict the outcome of the election. C4.5 algorithm model is a model that is easy to understand and has a good degree of accuracy. By using the C4.5 algorithm models the obtained results are of high accuracy values for the election results in the amount of 97.84% and the AUC value obtained is 0.970 with a diagnosis rate Excellent Classification